Efektivitas Strategi Pemasaran dan Layanan Hotel Sahid Raya Yogyakarta - M. Masrukhan; Cucu Rohendi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to analyze the effectiveness of marketing strategies and services at Sahid Raya Hotel Yogyakarta in improving customer satisfaction and competitiveness in the hospitality industry. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings indicate that digital marketing, such as social media and promotions on online platforms, significantly contributed to a 20% increase in occupancy rates within one year. Additionally, high service quality, including responsive service and staff friendliness, directly impacts customer loyalty. The main challenges identified include maintaining service quality amidst rising occupancy and intense competition. The study concludes that a combination of digital marketing strategies and effective service management is key to the hotel's success. Recommendations include strengthening customer loyalty programs, staff training, and continuous innovation to meet the demands of a dynamic market.